Digital Invasion or Digital Empowerment? The Role of Work-Life Balance in the Relationship between Digital Leadership and Employee Engagement (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2026)
This study seeks to investigate the direct impact of digital transformational leadership on employee engagement and to analyze the mediating function of work-life balance within higher education institutions in Medan. A quantitative methodology was utilized, employing a survey technique with a structured questionnaire disseminated to professors at higher education institutions in North Sumatra Province. The study's population and sample consisted of 120 permanent academics in North Sumatra Province. We utilized a questionnaire to collect data and Structural Equation Modeling (SEM) to analyze it. The findings indicated that digital transformative leadership exerted a favorable and significant impact on lecturer engagement. Nonetheless, work-life balance was not demonstrated to be a significant mediator or moderator in this relationship. This study demonstrates that within the framework of digital transformation, professor engagement is more significantly affected by leadership practices than by perceptions of work-life balance. Digital leadership that works can give teachers more power and make them more interested, but problems that come with the digital invasion need to be handled carefully. This study suggests that companies, particularly higher education institutions, should prioritize the enhancement of digital leadership capacity to sustain and elevate employee engagement in the digital age.